Efficacy of Carbon Microcoils in Relieving Cervicogenic Dizziness - Bittar,Roseli (2017)
Abstract Introduction Cervical pain contributes to postural deviations and imbalance. Nanotechnology may be used for the treatment of neck pain by fixing to the skin small rounds silicone patches containing double spiral carbon nanotubes arranged in the form of a coil (Helical), which would then relieve dizziness caused by muscular contraction. Objective The objective of this study is to Evaluate pain and dizziness scores before and after Helical patches effect on cervicogenic dizziness treatment. Methods The selected patients should have neck pain arising from muscle contraction with loss of balance or instability lasting more than 90 days and normal electrooculography. Treatment consisted of placing 10 Helical patches distributed as follows: two in the upper cervical area, two in the lower cervical area (near the 5th and 6th vertebrae), two in the upper trapezius muscle area (between neck and shoulder), and four in the tender point area (as reported by the patient). Using a Visual Analogue Scale (VAS), we matched pain and dizziness scores from Day 1 to those from Day 15 and Day 30 using Mann-Whitney test. Results There was a significant difference between pain score reported on Day 1 and Day 15 (Z = 2.43, U = 5, p = 0.01). We also found significant differences between dizziness scores reportedondays1 and15 (Z = 2.62, U = 3.5, p = 0.01) and days 1 and 30 (Z = 2.36, U = 5.5, p = 0.01). Conclusion The Helical patches seem to be an effective treatment for cervicogenic dizziness.